“Your Name Surrounded by Water”: The Fate of Locke's Island Atlantis - Farr, James (Locke Studies, 2025)
This essay begins with an intertextual study comparing Locke’s journal entries collectively entitled Atlantis with the Fundamental Constitutions of Carolina. It then proceeds at greater length to trace in maps and correspondence the appearance—and disappearance—of “Locke Island” as a cartographic name place and epistolary reference. Although the island bearing Locke’s name has been noted before, its story is untold in the detail that it deserves. Not only is it intrinsically interesting that an island in the new world—now known as Edisto Island—was once named for John Locke, but it is especially intriguing because of the fraught colonial politics attending it in the first place and especially the last. In particular, the disappearance of Locke Island from maps was a politically motivated cartographic erasure by one Maurice Mathews, a vindictive surveyor general at odds with the two principal Lords Proprietors for whom Locke worked as Secretary. Its story is also worth pursuing because—the coincidence is too hard to avoid, inviting conjecture—Locke Island was the very place in early colonial Carolina where Locke imagined an intentional community named Atlantis to be founded, however short-lived its fate.